AB1118 Procalcitonin differentiates infection from active disease in patients with juvenile idiopathic arthritis (JIA). (12th June 2018) - Trachtman, R.; Murray, E.T.; Pan, N.; Toussi, S.S.; Nellis, M.E.; Szymonifka, J.; Taber, S.F.; Adams, A.B.; Onel, K.B.; Mandl, L.A.
Abstract : Background: Patients with JIA often present with signs and symptoms suggestive of infection. However, differentiation of infectious from non-infectious presentation in routine clinical care is challenging. Procalcitonin (PCT) is a serum biomarker elevated in the setting of bacterial infection, but whether it can reliably differentiate infection from disease flare in patients with JIA is unknown.[ 1 Objectives: To test the hypothesis that PCT levels will differ between active JIA, quiescent JIA, bacteremic patients and healthy controls. Methods: From 10/16–4/17, consecutive children 6 months – 18 years with a) active untreated JIA b) quiescent JIA and c) healthy pre-surgical candidates were recruited from a musculoskeletal specialty hospital. JIA was defined according to ILAR criteria. Patients with active JIA despite treatment were excluded, to avoid confounding by treatment. Consecutive bacteremic patients were identified from an associated paediatric intensive care unit over the same period. Descriptive statistics and univariate logistic analyses were performed as appropriate. Results: Patient characteristics are summarised in Table 1; bacteremic patients were younger. PCT was elevated in bacteremic patients, and was undetectable in all other subjects (Table 2). There were trends towards higher ESR and CRP in bacteremic patients, but these were not statistically significant. Conclusions: Serum PCT levels appear to be a reliable biomarker to distinguish infection vs. active JIA at presentation, and can aid in directing therapy. However, PCT does not appear useful to assess disease activity in JIA. Further studies are needed to assess utility of serum PCT measurement in differentiating JIA flares from less severe infections. Reference: [1] Milcent K, et al., "Use of Procalcitonin Assays to Predict Serious Bacterial Infection in Young Febrile Infants, "JAMA Pediatrics170, no. 1 (2016): 62–69; Mohsen A, et al., "Predictive Values for Procalcitonin in the Diagnosis of Neonatal Sepsis, " Electronic Physician 7, no. 4 (2015): 1190–95. Disclosure of Interest: None declared